2020
DOI: 10.1111/jce.14369
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of atrial fibrillation reduces heart failure rehospitalization in patients with heart failure with preserved ejection fraction

Abstract: Background Atrial fibrillation (AF) is associated with heart failure (HF) rehospitalization in patients with heart failure with preserved ejection fraction (HFpEF). Objective We tested the hypothesis that catheter ablation of AF could reduce HF rehospitalization compared with conventional pharmacotherapy in patients with HFpEF. Methods Eighty‐five consecutive HFpEF (EF ≥ 50% and a history of HF hospitalization) patients diagnosed as AF by 12‐lead electrocardiogram were retrospectively analyzed. Thirty‐five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
65
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 20 publications
4
65
2
Order By: Relevance
“…8 Interestingly, none of the 27 patients in the ABL group who maintained sinus rhythm had HF hospitalization during follow-up and no major complication was observed with AF ablation in this relatively small group of patients. 8 Presented as one of the pioneering retrospective studies reporting the impact of catheter ablation of AF on reducing HF rehospitalization in AF-HFpEF, the authors should be congratulated for moving the needle forward in this field. As promising as the results seem, they should be examined carefully and placed in perspective.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…8 Interestingly, none of the 27 patients in the ABL group who maintained sinus rhythm had HF hospitalization during follow-up and no major complication was observed with AF ablation in this relatively small group of patients. 8 Presented as one of the pioneering retrospective studies reporting the impact of catheter ablation of AF on reducing HF rehospitalization in AF-HFpEF, the authors should be congratulated for moving the needle forward in this field. As promising as the results seem, they should be examined carefully and placed in perspective.…”
mentioning
confidence: 71%
“…8 Although no statistically significant increase in sinus rhythm maintenance was seen in the ABL group (P = .119), multivariate analysis revealed that AF ablation was the only preventive factor for HF rehospitalization (odds ratio = 0.15; P < .001). 8 Interestingly, none of the 27 patients in the ABL group who maintained sinus rhythm had HF hospitalization during follow-up and no major complication was observed with AF ablation in this relatively small group of patients. 8 Presented as one of the pioneering retrospective studies reporting the impact of catheter ablation of AF on reducing HF rehospitalization in AF-HFpEF, the authors should be congratulated for moving the needle forward in this field.…”
mentioning
confidence: 83%
See 3 more Smart Citations